Teaching introductory level VLSI design course to UNITEN undergraduate students - Ghazali A.; Hamid F.A. (2023)
VLSI design is a field which involves integrating very small devices on a very small piece of substrate. In Universiti Tenaga Nasional (UNITEN), an introduction to this field is offered as an elective course in the Bachelor of Electrical and Electronics Engineering program. The course is aimed to provide students a solid foundation in digital integrated circuit (IC) design. The content of this paper focuses mainly on course development, teaching methodologies and course assessment. The course outcomes are properly presented and they are reflected through discussions on the course contents and course assessment such as project, assignments and examinations. 2009 IEEE.